Predicting behavioural resistance to BIM implementation in construction projects: an empirical study integrating technology acceptance model and equity theory - Wang, Guangbin; Wang, Pengfei; Cao, Dongping; Luo, Xiaochun (Journal of Civil Engineering and Management, 2020)
Despite its great potential to streamline design and construction processes, the implementation of building information modelling (BIM) in many projects has failed to achieve expected benefits due to user resistance. Grounded in the technology acceptance model and equity theory, this study proposes a model of factors predicting resistance behaviours to BIM implementation during the post-adoption stage in construction projects. The model is tested with partial least squares modelling on survey data collected from design engineers in BIM-based construction projects in China. The empirical results provide evidence that after controlling for related individual, organizational and project characteristics, efficiency and equity perceptions play prominent but independent roles in determining behavioural resistance to BIM implementation, and that these perceptions are differently associated with contextual factors at individual, team and project levels. Apart from the independent contextual factors conceptualized in the model, control factors such as individual age and organization nature are also found to be significantly associated with resistance behaviours. As an exploratory effort to examine resistance behaviours to BIM implementation in construction projects, this study contributes to deepened understandings of the complexity of innovation resistance behaviours in the context of construction projects and offer suggestions for how to manage such behaviours.